2003
DOI: 10.1086/344612
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Planetary Nebulae in M51's Tidal Debris

Abstract: We report the results of a radial velocity survey of planetary nebulae (PNe) located in the tidal features of the well-known interacting system NGC 5194/95 (M51). We find clear kinematic evidence that M51's northwestern tidal debris consists of two discrete structures that overlap in projection-NGC 5195's own tidal tail and diffuse material stripped from NGC 5194. We compare these kinematic data to a new numerical simulation of the M51 system and show that the data are consistent with the classic '' single-pas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2003
2003
2005
2005

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 34 publications
3
40
0
Order By: Relevance
“…However, Durrell et al (2003) found, from a spectroscopic study of the kinematics of the planetary nebula system, that the kinematics of the northwestern tidal tails in M51 can be better explained by the single-passage models, while the receding component in the northwestern tidal tails is consistent with the results of the multiple-passage model given by Salo & Laurikainen (2000a;see their Fig. 5).…”
Section: Cluster Formation Associated With the Interaction Of Ngc 519supporting
confidence: 64%
See 2 more Smart Citations
“…However, Durrell et al (2003) found, from a spectroscopic study of the kinematics of the planetary nebula system, that the kinematics of the northwestern tidal tails in M51 can be better explained by the single-passage models, while the receding component in the northwestern tidal tails is consistent with the results of the multiple-passage model given by Salo & Laurikainen (2000a;see their Fig. 5).…”
Section: Cluster Formation Associated With the Interaction Of Ngc 519supporting
confidence: 64%
“…In the single-passage models first introduced by Toomre & Toomre (1972), the companion galaxy NGC 5195 crossed the NGC 5194 disk in the south at a distance of 25-30 kpc about 300-500 Myr ago (Hernquist 1990;Salo & Laurikainen 2000a;Durrell et al 2003). The model uses an adopted mass ratio of NGC 5195/NGC 5194 of 1 2 to 1 3 , consistent with observations (Schweizer 1977;Smith et al 1990).…”
Section: Cluster Formation Associated With the Interaction Of Ngc 519mentioning
confidence: 85%
See 1 more Smart Citation
“…The corresponding data for eight more systems from our list (object nos. 6,10,13,14,19,21,25, and 27; see Table 7 and Fig. 7 in Klimanov and Reshetnikov 2001) were taken from the LEDA and NED databases.…”
Section: Mean Parameters Of the Galaxy Samplementioning
confidence: 99%
“…Fortunately, the density of these extraordinary objects is relatively low, ∼ 1 arcmin −2 per unit redshift interval brighter than 5 × 10 −17 ergs cm −2 s −1 [30]. Thus while an occasional high-redshift interloper may be found within the body of a galaxy [31], these objects are unlikely to distort the shape of the luminosity function. The second source of confusion is specific to the Virgo Cluster.…”
Section: Planetary Nebula Identificationsmentioning
confidence: 98%